Alien plants of the Podilski Tovtry National Nature Park (Ukraine) - Lyubinska, Lyudmila (Biodiversity: Research and Conservation, 2010)
The results of a study on alien plants of the Podilsky Tovtry National Nature Park are presented. The alien fraction of the Park's flora comprises 335 species of vascular plants. Its taxonomic structure, ecological and life forms and species primary geographical origin are analyzed.